﻿Chronic toxicity assessment of nano-formulated Bischofia javanica leaves: Implications for pharmacological use - Cheryl Grace Pratiwi Rumahorbo; Syafruddin Ilyas; Salomo Hutahaean; Cut Fatimah Zuhra; Putri Cahaya Situmorang (Pensoft Publishers, 2023)
This study explores the chronic toxicity of nano-formulated Bischofia javanica leaves, a plant with pharmacological significance in Indonesia, following OECD guidelines 452. Graded doses (2, 4, 6, and 8 g/kg BW) of nano-formulated Bischofia javanica were administered to the treatment groups for 60 days, while the control group (K-) received only water. On the 61st day, the mice were euthanized, and samples for biochemical, hematological, and histopathological analysis were collected. Statistical analysis involved one-way ANOVA and Tukey's post hoc tests. Graded doses of nano-formulated Bischofia javanica leaves caused significant alterations in liver function. Doses between 2 and 4 g/kg BW improved liver histology and physiological markers. Higher doses (6 to 8 g/kg BW) led to liver dysfunction and histological degeneration, characterized by substantial fatty alterations, intracellular fat accumulation in hepatocytes, and compromised central blood vessels and sinusoids. The lungs showed signs of alveolar inflammation, epithelial exfoliation, debris, and the accumulation of inflammatory cells in alveolar spaces. Lower doses showed uniformly distributed cardiac blood vessels, while higher doses resulted in heart hemorrhages and amorphous exudates. Except for high doses, which significantly elevated specific liver damage indicators, no other levels of Bischofia javanica caused treatment-related mortality or significant alterations in hematological and biochemical parameters. Blood sugar levels remained stable across the dose range. In conclusion, moderate doses of nano-formulated Bischofia javanica leaf extracts can enhance physiological functions positively. However, caution is necessary when contemplating high doses, as they can cause dysfunction or damage vital organ systems.